2009
DOI: 10.3136/fstr.15.171
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Microplate-based .BETA.-carotene Bleaching Assay and Comparison of Antioxidant Activity (AOA) in Several Crops Measured by .BETA.-carotene Bleaching, DPPH and ORAC Assays

Abstract: The reproducibility and reliability of the micro-β-carotene-linoleic acid bleaching (BCB) assay have been improved, enabling comparison to the antioxidant activity (AOA) of extracts from eleven kinds of crops evaluated by the oxygen radical absorbance capacity (ORAC) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) assays. All assays were conducted using 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (Trolox) as a calibrator, and AOAs were expressed as micromoles of Trolox equivalent per gram of weight. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The DPPH free radical scavenging activity of the root extracts in the present study are also close to those reported for hydroalcoholic extracts [8]. For other extracts, comparisons are difficult because the data were not expressed as EC 50 , but as trolox equivalents [19] [43] [45]. A biologically more relevant way of evaluating the antioxidant activity is the inhibition of the mitochondrial ROS production.…”
Section: Discussionsupporting
confidence: 52%
“…The DPPH free radical scavenging activity of the root extracts in the present study are also close to those reported for hydroalcoholic extracts [8]. For other extracts, comparisons are difficult because the data were not expressed as EC 50 , but as trolox equivalents [19] [43] [45]. A biologically more relevant way of evaluating the antioxidant activity is the inhibition of the mitochondrial ROS production.…”
Section: Discussionsupporting
confidence: 52%
“…Except for AAPH, special grade chemicals were used in this experiment. dation in foods and biological systems (Mikami et al, 2009;Takebayashi et al, 2010;Wu et al, 2004b). In 2010, the USDA released the second database of the antioxidant capacity of 326 selected foods determined using ORAC methodology (iii).…”
Section: Introductionmentioning
confidence: 99%
“…ORAC assay ORAC assay was performed with modifications on a method based on Cao et al(1993), Huang et al(2002), Prior et al (2003) and Mikami et al(2009). In brief, AWA extracts and Trolox were diluted with 75 mM disodium phosphate buffer (pH 7.4).…”
Section: Plant Materials and Preparation Of Extracts Elevenmentioning
confidence: 99%